Construcción de un electrodo selectivo de cetirizina de membrana heterogénea - Araujo, Lilia; Prieto, Avismelsi; Cubillán, Dalia; Camargo, Nuris; Mercado, Jair; Naveda, Nildiana; Wilhelm, Nathalia (Ciencia, 1970)
Véase archivo PDF